Hydraulic characterization of field drip irrigation - D. Chamba; S. Zubelzu; L. Juana (Ingeniería del Agua)
Evaluation methods are analysed and proposed to determine in the field the emitter’s discharge equation, the head loss in laterals and submains pipe and distribution uniformity. Eight laterals dripline and one unit in the field at different pressures have been tested. The results shown that it is possible to determine the discharge curve and the manufacturing coefficient of variation with an accuracy similar to that of the standardised method, being able to be more representative that in the real facility. Concerning the head losses, the equivalent length presented values more independent of the flow than coefficient K that multiplies the kinematic term. The effect of the inlet pressure on the uniformity in the units and in the laterals was observed and, therefore, the operating pressure can be selected also considering the cost of energy. In conclusion, the proposed methods allow to characterise the hydraulic response of laterals, submain and the irrigation of the unit.